Fylogeografie komplexu Phasianus colchicus - Kofránek, Zdeněk (Jihočeská univerzita, 2020)
Genus Phasianus is currently divided into 2 species and 33 subspecies, which occupy a wide range from Japanese Islands to Caucasus Mts. This study deals with the phenotypic characters of Phasianus in order to reconstruct their evolution. The obtained results were compared with available molecular studies focused on the same group. In conclusion, phenotype characters of this genus serves us a sufficient number of phylogenetically informative characters, which fit well with their phylogenetic relationships.
Phylogeography of complex Phasianus colchicus
Keywords: Phasianus; bažant; poddruhy; fytogeografie; fenotypové znaky; fylogeneze; kladogram; Phasianus; pheasant; subspecies; phylogeography; phenotypic characteristic; phylogeny; cladogram